Effects of the Proactive Interdisciplinary Self-Management (PRISMA) Program on Online Care Platform Usage in Patients with Type 2 Diabetes in Primary Care: A Randomized Controlled Trial - Esther du Pon; Nanne Kleefstra; Frits Cleveringa; Ad van Dooren; Eibert R. Heerdink; Sandra van Dulmen (Journal of Diabetes Research)
Online care platforms can support patients with type 2 diabetes (T2DM) in managing their health. However, in the use of eHealth, a low participation rate is common. The Proactive Interdisciplinary Self-Management (PRISMA) program, aimed at improving patients’ self-management skills, was expected to encourage patients to manage their disease through the use of an online platform. Therefore, the objective of the current study was to investigate whether a group education program can improve the use of an online care platform in patients with T2DM treated by primary care providers in the Netherlands. In a randomized controlled trial, patients with T2DM received either PRISMA with usual care or usual care only. During a six-month follow-up period in 2014-2015, usage (number of log-ons and time spent per session) of an online care platform (e-Vita) aimed at improving T2DM self-management was assessed. A training about the functionalities of e-Vita was offered. The sample consisted of 203 patients. No differences were found between the intervention and control groups in the number of patients who attended the platform training (interested patients) (X21=0.58; p=0.45), and the number of patients who logged on at least once (platform users) (X21=0.46; p=0.50). In addition, no differences were found between the groups in the type of users—patients who logged on twice or more (active users) or patients who logged on once (nonactive users) (X21=0.56; p=0.45). The PRISMA program did not change platform usage in patients with T2DM. In addition, only a small proportion of the patients logged on twice or more. Patients probably need other encouragements to manage their condition using an online platform.